2017
DOI: 10.1167/iovs.17-21797
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin Films for Corneal Endothelial Regeneration: Transplant in a Rabbit Descemet Membrane Endothelial Keratoplasty

Abstract: We have developed SF films with biological properties that supported the growth of rabbit and human CECs, which showed normal morphology and characteristic markers; and with mechanical properties that allowed its use in a DMEK surgery, proving its in vivo functionality in a rabbit model of endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 59 publications
2
43
0
2
Order By: Relevance
“…); therefore, foreign body responses to silk-based implants and sutures might be expected. Various studies performed in rodents and large animals to evaluate silk fibroin biocompatibility across many different formats, including meshes ( 52 ), thin films ( 19 , 20 ), hydrogels ( 27 , 45 , 62 ), nanoparticles ( 63 65 ) and liquid solutions ( 23 , 25 ), have confirmed that silk fibroin induces no significant adverse responses, thereby substantiating the claims that silk fibroin is a biocompatible biopolymer. More importantly, these observations translate well to humans ( 1 ).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…); therefore, foreign body responses to silk-based implants and sutures might be expected. Various studies performed in rodents and large animals to evaluate silk fibroin biocompatibility across many different formats, including meshes ( 52 ), thin films ( 19 , 20 ), hydrogels ( 27 , 45 , 62 ), nanoparticles ( 63 65 ) and liquid solutions ( 23 , 25 ), have confirmed that silk fibroin induces no significant adverse responses, thereby substantiating the claims that silk fibroin is a biocompatible biopolymer. More importantly, these observations translate well to humans ( 1 ).…”
Section: Introductionmentioning
confidence: 72%
“… Vazquez et al . ( 20 ) B. mori ; 30 min; water-annealed under vacuum 24 h; sterilized 70% EtOH; silk film Descemet membrane replacement; substrate for human and rabbit corneal endothelial cells In vitro and in vivo , rabbits; tested transparency, gene expression, cell growth, integration and proliferation; no signs of immune rejection. Applegate et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have revealed the favourable biocompatibility of silk fibroin from B. mori and its excellent properties for use as a biomaterial in tissue engineering applications 39 41 , no cytocompatibility or biocompatibility studies are available for Tl- S, nor for any silk derived from mites. To test Tl- S cytocompatibility, we performed a study with silk films and nanoparticles of T. lintearius using the murine fibroblast cell line L929, which is commonly used in the evaluation of cytocompatibility and cytotoxicity of potential biomedical devices 42 .…”
Section: Resultsmentioning
confidence: 99%
“…The study demonstrated good support for the growth of human and rabbit corneal endothelial cells with the appropriate morphology and in vivo functionality after surgical implantation. [48] A fully synthetic hydrogel based on poly(ethylene glycol) and poly(caprolactone) (PCL) that are cross-linked with sebacic acid (Figure 7) has been studied as a substrate for corneal endothelial cell transplantation. [49] It has been shown to support excellent primary sheep corneal endothelial cell growth and monolayer formation with functional behavior after 7 d. Films of 50 µm thickness could be produced which had sufficient mechanical properties for surgical implantation into sheep eyes and this preliminary in vivo study demonstrated no adverse inflammatory response to the films with or without cells after 28 d. A similar in vitro response has been observed using a synthetic peptide based on poly(ε-lysine) cross-linked with nonanedioic acid with primary pig corneal endothelial cells (Figure 8).…”
Section: Endotheliummentioning
confidence: 99%